Development of an amperometric biosensor based on peroxidases to quantify citrinin in rice samples - Zachetti, Vanessa Gimena Lourdes (2013)
An amperometric biosensor based on horseradish peroxidase (EC1.11.1.7,H2O2-oxide-reductases) to determine the content of citrinin mycotoxin in rice samples is proposed by the first time. The method uses carbon paste electrodes filled up with multi-walled carbon nanotubes embedded in a mineral oil, horseradish peroxidase, and ferrocene as a redox mediator. The biosensor is covered externally with a dialysis membrane, which is fixed to the body side of the electrode with a Teflon laboratory film, and an O-ring. The reproducibility and the repeatability were of 7.0% and 3.0%, respectively, showing a very good biosensor performance. The calibration curve was linear in a concentration range from 1 to 11.6 nM. The limits of detection and quantification were 0.25 nM and 0.75 nM, respectively. For comparison, the citrinin content in rice samples was also determined by fluorimetric measurements. A very good correlation was obtained between the electrochemical and spectrophotometric methods.